Enamel hypoplasia and its correlation with dental caries in 12 and 15 years old school children in Shimla, India - Shailee Fotedar; G M Sogi; K R Sharma (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim was to assess the prevalence of enamel hypoplasia and its correlation with dental caries in 12 and 15 years old school children in Shimla city, Himachal Pradesh, India. Materials and Methods: This was a cross-sectional study conducted on a sample of 1011 school children aged ranging between 12 and 15 years old in Shimla city, Himachal Pradesh, India. A modified developmental defects of enamel index was used to classify the enamel defects. The statistical tests used was Chi-square tests. P < 0.05 was considered to be statistically significant. Results: The prevalence of enamel opacities was 18.2%. At 12 years of age, the prevalence was 17.9%, whereas at 15 years it was 18.6%. The tooth prevalence of enamel opacities of the entire sample was 11.8%. At 12 years tooth prevalence was 10.9% and at 15 years it was 12.7%. There was a significantly higher prevalence of Enamel hypoplasia among males at both the age groups. The diffuse type of enamel opacity was the most commonly seen at both the age groups. A significant association was found between caries and enamel opacities (P < 0.01). The occurrence of enamel opacities was statistically higher in children with the youngest mothers. Conclusions: The prevalence of enamel defects in this study is low when compared to National prevalence (22.3% at 12 years and 23.2% at 15 years). This study revealed a significant association between enamel defects and dental caries.